Transition to Adulthood - Young, Richard A. author. aut Link
IX, 235 p.
Keywords: It is widely accepted that the journey from youth to adulthood is a complex ongoing process. Not as clearly recognized is how goal directed and shared that journey actually is. Transition to Adulthood: Action, Projects, and Counseling brings both of these dimensions front and center in a contemporary practical perspective for viewing youth development, and for supporting young people as they attain adulthood. Focusing on the period from the end years of childhood through adolescence, and taking to task popular notions of children growing up too slowly or too quickly, the book’s contextual action theory capitalizes both on the individual’s agency in his/her development and on the social and cultural context provided by parents and other key figures. Chapters depict this transition as a non-linear rather than a strictly upward trajectory as young people prepare to enter such adult domains as decision-making, careers, autonomy, and intimacy. Instructive case examples and new study finding are included in these and other salient areas: • Emotions in the transition to adulthood • Establishing the adult identity • Romantic and intimate relationships • Transition in the context of disability • Suicide and suicidality in the transition • Counseling techniques, narrative and interpretation, the self-confrontation procedure Transition To Adulthood: Action, Projects, and Counseling offers researchers, therapists, counselors, and graduate students in developmental, clinical, counseling, and vocational psychology and social work a particular relevant lens for approaching this critical time in young people’s lives. “This book provides a powerful new framework for understanding individual youth as they take on the tasks associated with becoming adults – identity, love, career, life style, and meaning. Useful for both researchers and practitioners, this book could serve as an excellenttext for a course on the transition to adulthood, adolescence, or related topics.” – Reed W. Larson, University of Illinois, Urbana, IL “This extraordinary team of authors brings remarkable insight and years of research to bear on the many facets of the dynamic transition to adulthood. The book attends to the very social nature of this transition by skillfully applying an action theoretical perspective to compelling case material. This masterfully written book is destined to become a landmark. It is intellectual and at the same time accessible. Brilliant!” - Donna Schultheiss, Cleveland State University, Cleveland, OH .